THE EFFECT OF PLATELET RICH PLASMA ON MESENCHYMAL STEM CELLs (MSCs) DIFFERENTIATION INTO CHONDROBLAST - Dwikora Novembri Utomo; I Gde Adi Widiastana (Journal Orthopaedi and Traumatology Surabaya, 2017)
The addition of platelet rich plasma to mesenchymal stem cell culture on growth  media and  chondrogenic  media  had  any effect  on stem cell’s proliferation and differentiation into chondroblast has not been determined. This research is to find  out  the  effect  of  platelet  rich  plasma  on  mesenchymal  stem  cell’s differentiation and proliferation into chondroblast on in vitro media. Randomized control group posttest only design. Blood was taken from the rabbit’s vein to be processed into platelet rich plasma (PRP). Mesenchymal Stem Cell (MSC) was harvested from the bone marrow of the rabbit to be cultured. The MSC’s culture were divided into three groups of modification. The first group was combination of MSC added with Complete Culture Medium (CCM) and Chondrogenic Diferentation Medium (CDM) without PRP as control group. The second group had the same combination as the first group with extra 5% PRP. The third group had the same combination as the first group with extra 10% PRP. The results were evaluated in the following 21 days. The group that received extra 5% PRP had significant increase of chondroblast count compared to the group without PRP addition (p=0,033). The same result also occured on the groups that received extra 10% PRP compared to the group without PRP addition (p=0,028). There were no significant diferences between both the second and the third groupchondroblast count (p=0,203). There was a significant effect of platelet rich plasma on mesenchymal stem cell’s diferentiation and proliferation into chondroblast on invitro media.